2008
DOI: 10.1007/s10661-007-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treated sewage sludge levels on temporal variations of some soil properties of a Typic Xerofluvent soil in Menemen Plain, Western Anatolia, Turkey

Abstract: The aim of this study is to determine effects of treated sewage sludge (TSS) levels as an organic matter (OM) resource on temporal variations of some soil properties of a Typic Xerofluvent soil. The experiment was conducted in Menemen Plain, in the Western Anatolia Region of Turkey (latitudes 38 degrees 34'48.22''-38 degrees 34'49.24'' N; longitudes 27 degrees 1'23.05-27 degrees 1'24.14'' E) in the years of 2003 and 2004. Moist TSS was added to the soil at the rates of 0, 30, 60 and 90 t ha(-1) on May 1, 2003.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Treatments of increasing TSS levels significantly increased OM content of soil samples in the average of 5 periods. Analogously to our study, Delibacak et al (2009b) found out an increase in the concentrations of OM in soil caused by increasing doses of sewage sludge introduced to soil.…”
Section: Influence Of Tss Applications On Some Properties Of Sandy CLsupporting
confidence: 88%
“…Treatments of increasing TSS levels significantly increased OM content of soil samples in the average of 5 periods. Analogously to our study, Delibacak et al (2009b) found out an increase in the concentrations of OM in soil caused by increasing doses of sewage sludge introduced to soil.…”
Section: Influence Of Tss Applications On Some Properties Of Sandy CLsupporting
confidence: 88%
“…However, seasonal improvements and differences between seasons generally correlate better with OA quantity indicators (i.e., application rates) than with OA quality indicators (i.e., compositional properties). Other OA studies without combined mineral fertilizer applications have similarly observed the importance of OA application quantity over differences in OA type (Barzegar et al., 2002; Castellini et al., 2022; Delibacak et al., 2009; Tejada & Gonzalez, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…Yet little is known regarding the seasonal variability of OA impacts as most studies evaluate changes in soil properties at fixed yearly intervals (Cercioglu, 2017; Ferreras et al., 2006; Tejada & Gonzalez, 2008) or once at the end of an experiment (Li et al., 2018; Singh Brar et al., 2015; Yüksel & Kavdır, 2020; Zhao et al., 2009). Studies that do explore short‐term OA impacts observe strong seasonal fluctuations in the response of soil hydro‐physical properties to applications of OAs such as compost (Castellini et al., 2022; Felton, 1995), sewerage sludge (Delibacak et al., 2009), and biochar (Ouyang et al., 2013). These seasonal variations can furthermore differ strongly per soil hydro‐physical property (Zare et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient value of organic wastes is considered to be moderate (Petersen, 2001), although the variation in waste quality is large dependent on waste type and processing method (Smith et al 1998). Delibacak et al (2009), found that addition of increasing treated sewage sludge application to Typic Xerofluvent soil was significantly increased total salt, OM, total porosity, micro porosity, macro porosity, field capacity, wilting point, available water content, structure stability index and aggregation percentage values of soil when compared with control.…”
Section: Introductionmentioning
confidence: 99%